A Young Girl With Granulomatosis with Polyangiitis: A Rare Case Report (Bangladesh Journal of Medicine, 2023)
Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis is a necrotizing vasculitides that primarily affects small-sized arteries and manifests differently depending on the organ involved and the severity of the disease. Here we are reporting a case of a 15-year-old girl presented with purulent nasal discharge with epistaxis, cough, reduced hearing, fever & rash. Tissue biopsy report, positive C-ANCA, imaging and clinical features were consistent with the diagnosis of GPA. After counseling the patient & her parents and taking consent, she has been treated with intravenous methylprednisolone and cyclophosphamide. Despite being a rare disease with a typical age of onset around 40 years, it should be suspected in any aged patient exhibiting constitutional symptoms and other evidence of upper or lower respiratory tract involvement or glomerulonephritis.Bangladesh J Medicine 2023; 34(2): 151-154